PENDAMPINGAN SANTRI PUTRI PADA KEGIATAN TAHSIN AL QUR’AN DENGAN METODE JIBRIL DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Khulusinniyah; Farhatin Masruroh (As-Sidanah, 2019)
Tahsin Al Qur'an activities are carried out to optimize the learning of the Koran to students in Salafiyah Syafi'iyah Sukorejo Islamic boarding school. This activity is carried out outside formal pesantren education, as an effort to cover the shortage of Qur'an learning time in madrasas and hostel. In this activity, students are grouped based on their ability to read the Qur'an. The supervisor uses the Gabriel method as a learning method. The core of the implementation of the Gabriel method is the talqin-taqlid technique, (imitating), namely students imitating readings exemplified by the mentor, both classically, groups, and individuals. This can be done repeatedly until the santri master well in the readings and theories conveyed.